2011
DOI: 10.1159/000323096
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Protects Macrophages from Triglyceride Accumulation: Inhibitory Effect on DGAT1 Activity and on Triglyceride Biosynthesis

Abstract: Background/Aims: To analyze the effects of pomegranate juice (PJ) and punicalagin on macrophage triglyceride metabolism. Methods: Triglyceride metabolism was analyzed in PJ- or punicalagin-treated J774A.1 macrophages or in mouse peritoneal macrophages (MPM) harvested from C57BL/6 mice or from paraoxonase 2 (PON2)-deficient mice. Results: PJ (0–50 µM) significantly and dose-dependently decreased the triglyceride content and triglyceride biosynthesis rate in J774A.1 macrophages or in C57BL/6 MPM by about 30%. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 89 publications
2
17
0
Order By: Relevance
“…In searching for the selective beneficial characteristics of PJ in LCR vs. HCR rats, we further analyzed the above hypolidemic effect of PJ on macrophage lipids fluxes and observed a significant reduction in cellular uptake of LDL and Ox-LDL, as well as, a decrement in macrophage cholesterol biosynthesis rates, but with no significant effect on HDL –mediated cholesterol efflux from macrophages. Similar effects were observed in-vitro using a macrophage cell line [38, 39]. The stimulatory effect of PJ consumption on liver and heart lipids content, unlike the inhibitory effect of PJ on macrophage lipids mass, could be related to the liver lipids removal and to the heart energy requirements.…”
Section: Discussionsupporting
confidence: 67%
“…In searching for the selective beneficial characteristics of PJ in LCR vs. HCR rats, we further analyzed the above hypolidemic effect of PJ on macrophage lipids fluxes and observed a significant reduction in cellular uptake of LDL and Ox-LDL, as well as, a decrement in macrophage cholesterol biosynthesis rates, but with no significant effect on HDL –mediated cholesterol efflux from macrophages. Similar effects were observed in-vitro using a macrophage cell line [38, 39]. The stimulatory effect of PJ consumption on liver and heart lipids content, unlike the inhibitory effect of PJ on macrophage lipids mass, could be related to the liver lipids removal and to the heart energy requirements.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, treatment of J774A.1 with AAPH was found to increase macrophage ROS generation and the accumulation of triglycerides [45]. Various anti-oxidants were shown to attenuate the accumulation of triglycerides, including recombinant PON2, the NADPH-oxidase inhibitor apocynin, or pomegranate polyphenols; all inhibited the enhanced rate of triglyceride biosynthesis and the activation of DGAT1 under the above prooxidative conditions [44,48,52]. Increased oxidative stress was also shown to be associated with inhibition of triglyceride hydrolysis as demonstrated by exposure of J774A.1 macrophages to silicon dioxide nanoparticles, resulting in increased ROS generation and triglyceride accumulation via attenuated triglyceride hydrolysis rate and down-regulation of HSL and ATGL [46].…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Hamoud et al [26], consumption of pomegranate extract pill (POMx) in simvastatin treated hypercholesterolemic patients significantly reduced macrophage TG content by 48% and human monocyte-derived macrophages cholesterol biosynthesis rate by 33%. Pomegranate juice and punicalagin were both shown to inhibit TG biosynthesis, via the rate limiting enzyme diacylglycerol O-acyltransferase 1(DGAT1) [27]. It was previously shown that pomegranate juice inhibits oxidized LDL uptake and macrophage cholesterol biosynthesis and also downstream the HMGCoA-reductase [28].…”
Section: Discussionmentioning
confidence: 99%